Geochemical imprints of genotypic variants of Globigerina bulloides in the Arabian Sea. (29th October 2016) - Sadekov, Aleksey Yu.; Darling, Kate F.; Ishimura, Toyoho; Wade, Christopher M.; Kimoto, Katsunori; Singh, Arun Deo; Anand, Pallavi; Kroon, Dick; Jung, Simon; Ganssen, Gerald; Ganeshram, Raja; Tsunogai, Urumu; et al.
Abstract: Planktonic foraminifera record oceanic conditions in their shell geochemistry. Many palaeoenvironmental studies have used fossil planktonic foraminifera to constrain past seawater properties by defining species based on their shell morphology. Recent genetic studies, however, have identified ecologically distinct genotypes within traditionally recognized morphospecies, signaling potential repercussions for palaeoclimate reconstructions. Here we demonstrate how the presence of Globigerina bulloides cryptic genotypes in the Arabian Sea may influence geochemical signals of living and fossil assemblages of these morphospecies. We have identified two distinct genotypes of G. bulloides with either cool water (type‐II) or warm water (type‐I) temperature preferences in the Western Arabian Sea. We accompany these genetic studies with analyses of Mg/Ca and stable oxygen isotope (δ 18 O) compositions of individual G. bulloides shells. Both Mg/Ca and δ 18 O values display bimodal distribution patterns. The distribution of Mg/Ca values cannot be simply explained by seawater parameters, and we attribute it to genotype‐specific biological controls on the shell geochemistry. The wide range of δ 18 O values in the fossil assemblage also suggests that similar controls likely influence this proxy in addition to environmental parameters. However, the magnitude of this effect on the δ 18 O signals is not clear from our data set, and further work is needed to clarify this. We also discuss current evidence of potential genotype‐specific geochemical signals in published data on G. bulloides geochemistry and other planktonic foraminiferal species. We conclude that significant caution should be taken when utilizing G. bulloides geochemistry for paleoclimate reconstruction in the regions with upwelling activity or oceanographic fronts. Key Points: Two coexisting genotypes of Globigerina bulloides in the Arabian Sea Both stable oxygen isotope and Mg/Ca compositions of individual G. bulloides shells have bimodal distributions Genetic variability affects foraminiferal geochemistry